This strange eventful history : a novel - Messud, Claire, 1966- (W.W. Norton & Company, 2024)
Inspired in part by long-ago stories from her own family's history, this masterful story follows the Cassars over seven decades, starting with patriarch Gaston and his wife Lucienne, whose myth of perfect love sustains them, and ending with Chloe, who believes telling her family's buried stories will bring them all peace.